An overview on 1,2,4-triazole and 1,3,4-thiadiazole derivatives as potential anesthesic and anti-inflammatory agents - Koval, Andriy; Lozynskyi, Andrii; Shtrygol’, Sergiy; Lesyk, Roman (ScienceRise: Pharmaceutical Science, 2022)
The aim. The purpose of this review is to summarize data on the synthesis and structural modification of heterocyclic systems with triazole and thiadiazole fragments in molecules as promising objects in bioorganic and medicinal chemistry. Materials and methods. The research based on bibliosemantic and analytical methods using bibliographic and abstract databases, as well as databases of chemical compounds. Results. Modern medicinal chemistry faces many challenges, one of which is the determination of the activity and specificity of therapeutic agents. Recent scientific data showed that triazoles and/or thiadiazoles have broad spectrum of biological activities, in particular antimicrobial, antifungal, antiviral, anticancer and anticonvulsant. Synthetic research allows to propose a whole number of new molecular design directions of biological active triazole and/or thiadiazole derivatives, as well as to obtain directed library that include hundreds of new compounds. This review is an effort to summarize data of its analgesic and anti-inflammatory activity over the last decade. We summarized and analyzed the series of triazole and/or thiadiazole derivatives and provided data of their structure-activity relationship. For optimization and rational design of highly active molecules with optimal «drug-like» characteristics and discovering of possible mechanism of action SAR, QSAR analysis and molecular docking were summarized. Conclusions. It has been shown that heterocyclic systems containing fragments of triazole and / or thiadiazole are a significant source of promising analgesic and/or anti-inflammatory agents. It has been established that the mentioned heterocyclic derivatives have a high selectivity of action, low toxicity and an effect commensurate with standard drugs